Strategi Implementatif KKNI dalam Pembelajaran Pendidikan Islam di IAIN Curup - Warsah, Idi; Imron, Imron; Siswanto, Siswanto; Sendi, Okni Aisa Mutiara (Universitas Muhammadiyah Magelang, 2020)
Since 2017, KKNI as a national curriculum at a university level has been implemented in the overall departments at IAIN Curup, Bengkulu. Principally, the implementation of KKNI depends upon the implementative strategies by the lecturers. The present study sought to investigate the implementative strategies of KKNI curriculum by the lectutrers in Islamic education (PAI) department at IAIN Curup as well as the influencial and impeding factors. This study adopted a qualitative approach using in-depth inteview as the data collection technique. The data were analyzed based upon interactive model comprising data collection, data condensation, data display, and verifying conclusion. This study revealed that the KKNI implementative strategies were adequately good and had covered KKNI elements. RPS preparation had conformed to the guidance of KKNI. The preparation of learning media, the application of interesting learning methods, and learning evaluations had rested upon learning environments. In addition, learning evaluations had been aligned with the goals set. The influential factors of KKNI implementation ranged from the sufficient availability of library books, internet availability, the presence of professional lecturers, the establishment of international cooperative learning, to comfortable environments. However, the factor impeding the attainment of learning with KKNI was PAI students’ motivation that was still low in digging information from literatures either online or offline.